Developing and Supporting the Diversity of Chairperson Roles - Jean Pawl; Richard Griner; Deborah Richardson; Elizabeth Nesmith (Academic Chairpersons Conference Proceedings, 2017)
A monthly Chair Professional Development program at Augusta University provides opportunity to mentor new chairpersons and foster collegiality amongst all chairpersons at a university with both liberal arts and health sciences programs. The merits and challenges of this program that addresses needs of such a diverse group will be highlighted
Keywords: Professional Development; Diversity; Mentoring; Collegiality